2021
DOI: 10.3389/fphar.2021.746391
|View full text |Cite
|
Sign up to set email alerts
|

Icariin Alleviates Wear Particle-Induced Periprosthetic Osteolysis via Down-Regulation of the Estrogen Receptor α-mediated NF-κB Signaling Pathway in Macrophages

Abstract: Periprosthetic osteolysis is one of the major long-term complications following total joint replacement. Its cause is widely accepted to be wear particle-induced activation of inflammatory macrophages. No effective strategy for the prevention and treatment of periprosthetic osteolysis is yet available. Recently, considerable evidence has shown that icariin effectively protects against estrogen deficiency-related bone loss and bone deterioration. However, the molecular mechanism underlying the inhibitory effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Based on the inhibitory effects of METTL3 silencing on inflammatory osteoclast differentiation and bone resorption in vitro, further experiments were performed to explore the potential role of METTL3 in pathological bone loss in vivo. We constructed an LPS-induced cranial osteolysis mouse model, as previously described, and locally injected lentivirus-carrying shRNAs [ 56 , 57 ]. As evaluated through Micro-CT scanning, the injection of lentivirus-carrying Mettl3 -shRNA significantly suppressed LPS-induced osteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the inhibitory effects of METTL3 silencing on inflammatory osteoclast differentiation and bone resorption in vitro, further experiments were performed to explore the potential role of METTL3 in pathological bone loss in vivo. We constructed an LPS-induced cranial osteolysis mouse model, as previously described, and locally injected lentivirus-carrying shRNAs [ 56 , 57 ]. As evaluated through Micro-CT scanning, the injection of lentivirus-carrying Mettl3 -shRNA significantly suppressed LPS-induced osteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that some compounds from Chinese herbal medicines can treat particle-induced osteolysis by inhibiting the modules in the NF-κB signaling pathway, the main mechanism in the regulation of osteolysis, to effect the balance of osteoclasts and osteoblasts [ 12 , 45 , 50 , 61 , 68 ]. WDL is known for its ability to block the phosphorylation of IκBα, which acts to regulate the transcription of NF-κB mediated genes, inhibiting LPS-induced pro-inflammation [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the ratio of RANKL/OPG increases, the osteoclast precursors are easier influenced by RANKL signaling through the downstream activation of NF-κB/c-fos/NFATc1, subsequently causing the precursors to differentiate into mature osteoclasts. On the other hand, macrophages also plays a key role in wear particle-induced osteolysis [63,[65][66][67][68]. Cytokines (TNF-α and IL-1β, etc.)…”
Section: Et Al Also Indicated That Traditional Mixed Extracts Of Medi...mentioning
confidence: 99%
“…Therefore, IKK inhibitors reduce LPS-induced expressions of IL-1, IL-6, IL-10, TNF-a, and IFN (204). Recent studies have revealed that diverse wear particles (e.g., Ti, TiPs, HA, PE, PMMA) could induce the macrophage to release proinflammatory cytokines and chemokines, which are accomplished by the activation of NF-kB signaling pathways and associated macrophage polarization (15,26,54,205). Qiu et al found that stimulation of LPS or Ti particles could up-regulate p-IKKb, p-IkBa, and p-p65 and significantly increase the translocation of p65 into the nucleus in BMDMs.…”
Section: Nf-kb Signaling In Macrophage Polarizationmentioning
confidence: 99%